Impaired Exercise Performance and Skeletal Muscle Mitochondrial Function in Rats with Secondary Carnitine Deficiency - Bouitbir, Jamal; Haegler, Patrizia; Singh, François; Joerin, Lorenz; Felser, Andrea; Duthaler, Urs; Krähenbühl, Stephan (Frontiers in Physiology, 2016)
Purpose: The effects of carnitine depletion upon exercise performance and skeletal muscle mitochondrial function remain largely unexplored. We therefore investigated the effect of N-trimethyl-hydrazine-3-propionate (THP), a carnitine analogue inhibiting carnitine biosynthesis and renal carnitine reabsorption, on physical performance and skeletal muscle mitochondrial function in rats. Methods: Male Sprague Dawley rats were treated daily with water (control rats; n=12) or with 20 mg/100 g body weight THP (n=12) via oral gavage for 3 weeks. Following treatment, half of the animals of each group performed an exercise test until exhaustion. Results: Distance covered and exercise performance were lower in THP-treated compared to control rats. In the oxidative soleus muscle, carnitine depletion caused atrophy (-24%) and impaired function of complex II and IV of the mitochondrial electron transport chain. The free radical leak (ROS production relative to oxygen consumption) was increased and the cellular glutathione pool decreased. Moreover, mRNA expression of markers of mitochondrial biogenesis and mitochondrial DNA were decreased in THP-treated compared to control rats. In comparison, in the glycolytic gastrocnemius muscle, carnitine depletion was associated with impaired function of complex IV and increased free radical leak, whilst muscle weight and cellular glutathione pool were maintained. Markers of mitochondrial proliferation and mitochondrial DNA were unaffected. Conclusions: Carnitine deficiency is associated with impaired exercise capacity in rats treated with THP. THP-induced carnitine deficiency is associated with impaired function of the electron transport chain in oxidative and glycolytic muscle as well as with atrophy and decreased mitochondrial DNA in oxidative muscle.